MODELLING EXPERT SYSTEM FOR LUNG DISEASE. (July 2020) - Riskiawan, H Y; Rizaldi, T; Setyohadi, D P S; Utami, M M D
Abstract: One of the vital organs in humans is the lungs. Lungs infected with the disease and not or late diagnosed can cause fatal conditions that have the potential to cause death. The rapid development of artificial intelligence, especially the expert system, is one of the solutions for the early diagnosis of respiratory diseases, especially in the lungs. By applying the forward chaining method that analyzes the facts given by the user to determine the diagnosis results, the expert system for lung disease that was built focused on six lung diseases that are common in Indonesia.